Crime, corruption, and development - Narasimha Reddy, D.; Indian Economic Association. Conference 2000-2001 : Jammu University) (New Delhi : Deep & Deep publications, 2001)
Contributed articles presented at 83rd annual conference of the Indian Economic Association held at Jammu University during Dec. 30-31, 2000 and January 1, 2001.
S/Pensyarah/Rastech
Includes bibliographical references (p. [230]-262) and index.
Keywords: Political corruption -- India -- Congresses; Business enterprises -- India -- Congresses; Bribery -- India -- Congresses